Assessment of equivalent thermal properties of multilayer building walls coupling simulations and experimental measurements. (January 2018) - Evangelisti, Luca; Guattari, Claudia; Gori, Paola; Asdrubali, Francesco
Abstract: The growing effort of reducing energy needs in the building sector calls for an accurate characterization of the performances of external walls, which are the main cause of thermal exchanges and consequently are fundamental to realize accurate simulation models to evaluate and control thermal loads. The dynamic characterization of a multilayer wall can be performed by defining its stratigraphy and the thermo-physical parameters of each layer. When existing buildings are investigated, technical specifications may be unknown or difficult to obtain due to documents lost over time; furthermore, aging may have altered the building materials characteristics. In these cases, in-situ measurements become essential but there is the need to analyze the behavior of walls considering their dynamic characteristics, not obtainable by employing non-destructive tests, such as the heat-flow meter method. The paper aims to verify if an equivalent homogeneous wall can be associated to a multilayer wall in the sense of producing the same behavior if exposed to the same outdoor environmental conditions. Findings in literature demonstrate that, generally, this is not exactly achievable. However, the possibility of an approximate equivalence is investigated in this work by means of finite-element simulations and experimental measurements. The results obtained in actual case studies show that this equivalence can be made, obtaining preliminary satisfying results. The proposed methodology can be employed in existing and historical buildings to achieve useful equivalent data directly applicable for the energy retrofit phase and for achieving a better coupling between the building and the heating/cooling system, reducing environmental impacts. Highlights: Method useful to retrofit existing and historical buildings. Method able to provide equivalent data directly applicable for the energy retrofit. The approach overcomes significant simulation parameters uncertainty/inaccuracies. Better building-plant coupling, reducing emissions and environmental impact.